The Philippines in a Liberalizing Trade Environment: Issues and Prospects - Patalinghug, Jason (Economic Insights - Trends & Challenges, 2020)
Free trade agreements (FTAs) have mushroomed in the Asia-Pacific region over the past fifteen years. The Philippines is trying to forge several of these agreements in order to stay competitive. This paper examines the emergence of the Association of South East Asian Nations (ASEAN) as well as the ASEAN Free Trade Agreement. This paper will discuss the advantages for the country by joining both the AFTA and the Japan Philippines Economic Partnership Agreement. It will also discuss several free trade agreements that are in effect in the region as well as efforts by the country to join the Trans-Pacific Partnership (TPP) and the Regional Comprehensive Economic Partnership (RCEP). For the country to be a member of the TPP certain institutional reforms are needed to be put in place. The studies examined in this paper show that these FTAs in general have a positive effect on the Philippine economy.
Keywords: PHILIPPINES; REGIONAL Comprehensive Economic PartnershipCOMMERCIAL treatiesTRANS-Pacific PartnershipFREE tradePARTNERSHIP agreements; dept.eco; peer-reviewed; ⛔ No DOI found